Healthy Tourism Village Education based on Sustainable Development Goals (SDGs) in Kenagarian Singkarak Regency Solok - Nugroho Susanto; Windo Wiriadinata; Nuridin Widya Pranoto (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Village SDGs is a sustainable development role that is included in the priority program for using village funds in 2021. Koto One of the tourism potentials in Koto Specifically, the existing problems are (1) The health sector in the Koto (2) Seeing environmental conditions and the lack of awareness of the local community, the existing Lake Singkarak area receives less attention and is not well maintained, making it less attractive to visitors (3). Lack of human resources (HR) capable of managing tourism potential. (4) There are no SOPs and tourism health protocols in this area. The methods used are education and training, forming tourist village cadres, mentoring and helping to complete health facilities and infrastructure in tourist villages. The results of the activity are increased public knowledge and awareness about the importance of cleanliness and comfort at tourist sites, increased knowledge of food handlers regarding hygiene and sanitation, the provision of health infrastructure at tourist sites, and the establishment of university and village partnerships.